A brief history of statistical developments in animal breeding 2 - use of genomics in animal breeding practice - Gianola, Daniel (Henry Stewart Talks, 2017)
Setting the state for the genomics era, Dealing with epistatic interactions, Machine learning: largely non-parametric, Challenges: sequence information, bigger data, and causality